2019
DOI: 10.3390/ijerph16111908
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Earthworm Impacts on Soil Organic Carbon under Different Tillage Systems

Abstract: Previous research has shown the varied effect of earthworms on soil carbon dynamics. We carried out a 180-day incubation experiment with earthworms and maize residue additions under conventional tillage (CT) and no tillage (NT) system conditions to quantify the earthworm effect in the black soil of northeastern China. Earthworms did not affect soil CO2 emissions, while residue addition significantly increased such emissions. The effects of earthworms on dissolved organic carbon (DOC) and microbial biomass carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…The lack of a significant "earthworm effect" could be due to the fact that our mesocosm experiment did not include the return of aboveground plant residues, which was the usual practice in the INT and ORG systems. Both epigeic and anecic earthworms prefer to consume the surface plant remains instead of the C stored in the soil, and by incorporating this new C down the profile and casting, they significantly enhance soil C stabilization (Zhang et al, 2013;Guo et al, 2019). Despite these limitations, our study showed that intensive managements not only had detrimental effects on the composition and structure of soil detrital food webs by favoring smaller sized organisms against macrofauna in agreement with previous studies (Tsiafouli et al, 2015;Lago et al, 2019), but also led to significantly greater amounts of C being lost from these soils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a significant "earthworm effect" could be due to the fact that our mesocosm experiment did not include the return of aboveground plant residues, which was the usual practice in the INT and ORG systems. Both epigeic and anecic earthworms prefer to consume the surface plant remains instead of the C stored in the soil, and by incorporating this new C down the profile and casting, they significantly enhance soil C stabilization (Zhang et al, 2013;Guo et al, 2019). Despite these limitations, our study showed that intensive managements not only had detrimental effects on the composition and structure of soil detrital food webs by favoring smaller sized organisms against macrofauna in agreement with previous studies (Tsiafouli et al, 2015;Lago et al, 2019), but also led to significantly greater amounts of C being lost from these soils.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, in this study, more CO 2 and DOC were lost from the CONV managed soils with the highest values of microbial biomass. Because microorganisms use DOC to produce their microbial biomass (Guo et al, 2019), a gradual decrease of the DOC/DON ratio was observed over time. This implies that CONV agricultural practices would not only contribute to increased soil respiration rates, but they could also lead to soil organic C depletion in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tillage depth under STF increased to 30–40 cm, fewer crop residues were incorporated at this depth because the soil was loosened rather than turned over. Therefore, the higher SOC concentration under NTF and STF than that under PTF at 0–10 cm may have been due to sufficient carbon inputs from crop residues [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earthworms are widely distributed in soil [11,12]. There is much evidence to prove the importance of earthworms in ecosystem functioning [13][14][15]. In previous research, Wang et al [11] used a filter paper method to determine the toxicity of neonicotinoids to earthworms and found that compared with other pesticides, nicotinic insecticides showed higher toxicity to earthworms.…”
Section: Introductionmentioning
confidence: 99%